1996
DOI: 10.1139/b96-033
|View full text |Cite
|
Sign up to set email alerts
|

Response of root and cotton strip decay to nitrogen amendment along a barrier island dune chronosequence

Abstract: The influence of nitrogen amendment on fine root decomposition was evaluated on sites located along a barrier island chronosequence (24-, 36-, and 120-year-old dunes). The degree to which exogenous nitrogen limits decay at each site was evaluated through a fertilization experiment. Decay substrates included native roots and cotton strips that differed in carbon and nitrogen chemistries. Root decay on younger sites (24 and 36 years old) showed a slight but significant increase in native root decay in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Each value represents a composite sample from four replicates rienced net release. The high levels of N immobilization in roots contrast with the low N immobilization potential of roots in tallgrass prairies (Seastedt et al 1992), but the occurrence of P release is in agreement with other studies (Seastedt 1988;Conn and Day 1996). The ability of roots to decompose faster than leaves but to retain N may indicate that roots serve an important role in N retention in these forests.…”
Section: Figsupporting
confidence: 89%
See 3 more Smart Citations
“…Each value represents a composite sample from four replicates rienced net release. The high levels of N immobilization in roots contrast with the low N immobilization potential of roots in tallgrass prairies (Seastedt et al 1992), but the occurrence of P release is in agreement with other studies (Seastedt 1988;Conn and Day 1996). The ability of roots to decompose faster than leaves but to retain N may indicate that roots serve an important role in N retention in these forests.…”
Section: Figsupporting
confidence: 89%
“…These results suggest that N and P limit root decomposition at the old, 4.1-Myear-old site, but not in the young, 300-year-old soils. The only other study that has examined root decay after N-fertilization found enhanced mass loss on two young dune sites but not on the oldest dune site (Conn and Day 1996).…”
Section: Nutrient Limitations To Decomposition: Effects Of Soil Fertimentioning
confidence: 87%
See 2 more Smart Citations
“…However, traditional research on these relationships has focused primarily on the aboveground plant tissues such as foliage (Hobbie 2008;Perakis et al 2012). Although a growing body of studies suggest that root-derived materials may contribute more to stabilizing soil organic matter than foliage (Rasse et al 2005;Crow et al 2009), empirical evidence for the effect of increased N availability on the afterlife of fine roots remains lacking (Conn and Day 1996;Ostertag and Hobbie 1999;Mao et al 2011;Norris et al 2013;Solly et al 2014). This, to a large extent, impedes further understanding of the responses of plant tissue decomposition to increased N availability on a broader scale, and the underlying response mechanisms.…”
Section: Introductionmentioning
confidence: 99%